Fonologi Al-Qur’an Pada Surah Asy-Syamsy Analisis Keserasian Bunyi Pada Sajak dan Efek Yang Ditimbulkannya - Gunarti, Tri Tami (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2020)
One of the advantages possessed by the Al-Quran is the use of a beautiful language style, a series of letters and sounds that are so harmonious between the vowels and the consonants and the regularity of the verses creates a beautiful harmony, because the Koran is a recited text. Therefore, to find out the beauty of the language style contained in the Koran, it is necessary to study the principles of the Koran using a linguistic approach. This is very important, to know and understand the message content in the Koran and the beauty of lafadz and its meaning. Thus one of the studies carried out is through the study of the beauty of lafadz which is included in the study of balaghah or badi 'science. The harmony of the sound of the last letter in the verses of the surah asy syamsy is discussed in this writing, as well as the effects it causes. This harmony in balaghah is called rhyme. The harmony of sounds in surah ash-Shamsy is found in verses 1-15, the effect that is generated includes the effect of phonology on harmony and the effect of phonology on meaning.